Artificial Ageing of Aeronautical Al-Cu-Li (2198) Sheets: Mechanical Behaviour and Corrosion Susceptibility - Nikolaos D. Alexopoulos (Engineering Proceedings, 2025)
In the present article, the effect of artificial ageing on tensile mechanical properties and resistance to corrosion of aluminium alloy 2198-T3 was investigated. The results were obtained under the framework of the Greek National project “CorLi”, which was targeted to document the mechanical behaviour of the alloy under different artificial ageing conditions, simulating the natural ageing of aircraft structures during their operation lifespan. Four (4) different ageing conditions corresponding to under-aged (UA), peak-aged (PA), and over-aged (OA) tempers based on the initial, T3 temper, were considered. In the PA condition, the conventional yield stress Rp0.2% increased by more than 50% with a simultaneous 46% decrease in tensile elongation at fracture Af. Additionally, the effect of corrosion was found to be different for the different artificial ageing tempers of AA2198, with lower charge transfer resistance (RCT) observed for artificially aged specimens. Nevertheless, the corrosion-induced degradation rate of RCT was found to decrease with increasing ageing time.